2017
DOI: 10.1002/nau.23374
|View full text |Cite
|
Sign up to set email alerts
|

The role of C‐fibers in the development of chronic psychological stress induced enhanced bladder sensations and nociceptive responses: A multidisciplinary approach to the study of urologic chronic pelvic pain syndrome (MAPP) research network study

Abstract: Chronic WAS induced bladder hypersensitivity manifested by earlier voiding with earlier VMR appearance. Chronic stress also enhanced bladder nociceptive responses. WAS leads to increase responses to ice cold water infusion, implying a role of sensitized C-fibers and mechanoreceptors in WAS-induced bladder dysfunction and hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…Similarly, in animal models (WAS, chronic social defeat, and social stress), chronic stress results in visceral hypersensitivity and alterations in structure and function of the urinary bladder . These include bladder wall remodeling, mast cell infiltration and angiogenesis, increased voiding frequency, reduced voided volume, and increased visceral hypersensitivity during bladder filling . Our study provides the foundation for a mechanism linking these stressors to bladder abnormalities through changes in the urothelial mitochondria.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Similarly, in animal models (WAS, chronic social defeat, and social stress), chronic stress results in visceral hypersensitivity and alterations in structure and function of the urinary bladder . These include bladder wall remodeling, mast cell infiltration and angiogenesis, increased voiding frequency, reduced voided volume, and increased visceral hypersensitivity during bladder filling . Our study provides the foundation for a mechanism linking these stressors to bladder abnormalities through changes in the urothelial mitochondria.…”
Section: Discussionmentioning
confidence: 65%
“…[12][13][14] These include bladder wall remodeling, mast cell infiltration and angiogenesis, increased voiding frequency, reduced voided volume, and increased visceral hypersensitivity during bladder filling. [9][10][11][12][13][14] Our study provides the foundation for a mechanism linking these stressors to bladder abnormalities through changes in the urothelial mitochondria. A main finding of our study was a more depolarized Ψm which was associated with a tendency toward increased SRC and maximal respiration.…”
Section: Chronic Stress Effects On Bladder Function and Visceral Sementioning
confidence: 82%
See 1 more Smart Citation
“…Chronic WAS is another well‐known model highly relevant to human IC/BPS without Hunner lesions. Rats exposed to WAS showed bladder hypersensitivity symptoms including a decreased threshold of micturition, increased urinary frequency and hyperalgesia 134–136 . The rats also showed increased subepithelial MC infiltration and urinary NGF levels, 137,138 with increased engagement and connectivity of brain micturition neuronal circuits and motor cortex regions 135 .…”
Section: Animal Modelsmentioning
confidence: 99%
“…14,15 Consistent with this, the MAPP research network has recently identified potential central biological markers for IC/BPS, which include functional alterations in a sensorimotor network, abnormal connectivity of posterior medial cortex, and brain microstructural changes associated with chronic pain, bladder function, and symptom severity. [16][17][18][19][20][21][22][23][24] Our prior work [25][26][27][28][29] has employed a reverse translational rodent model that parallels the clinical phenotype of IC/BPS, in particular the role of chronic stress in the development and maintenance of urinary symptoms and bladder hypersensitivity, 2,[30][31][32][33][34] as well as general pain sensitivity in susceptible individuals predisposed to anxiety. 8,[35][36][37][38][39] In this model, we have demonstrated that chronic water avoidance stress (WAS) leads to urinary frequency, bladder hyperalgesia, and increased somatosensory nociceptive reflex responses that persist up to 1 month following removal of the stressor.…”
Section: Introductionmentioning
confidence: 99%